PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID UNTUK VISUALISASI BANGUN RUANG PADA MAHASISWA PGSD SEMESTER III STKIP AGAMA HINDU AMLAPURA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop an interactive learning media based on Android for visualizing spatial geometry on third-semester PGSD students at STKIP Agama Hindu Amlapura. The learning media is expected to help students understand the abstract concepts of space geometry, which are often difficult to grasp. The development of this media follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to ensure the quality and effectiveness of the application. The media is designed with a user-friendly interface and includes 3D visualizations of spatial shapes such as cubes, spheres, and pyramids, which can be rotated to provide a clearer understanding. In the evaluation stage, the application was tested by PGSD students to assess its effectiveness in improving their understanding of spatial geometry. The results show that this Android-based learning media significantly enhances students' understanding of spatial geometry. Additionally, the application is considered practical and effective, with positive feedback from students regarding its convenience for use anytime and anywhere. Based on these results, it is recommended that this Android-based learning media be further developed and implemented in higher education, particularly for courses requiring 3D visualization.